Cholangiocarcinoma presenting as a solitary epididymal metastasis: a case report and review of the literature - Bailey David M; Bennett Victoria S (BMC, 2007)
Abstract Background Solid tumor metastasis to the epididymis is a rare occurrence and is mostly discovered incidentally at autopsy or after therapeutic orchidectomy for prostate cancer. Other primary carcinomas that have been demonstrated to metastasize to the paratesticular region include those originating in the stomach, kidney, ileum, and colon. Case presentation A 72-year-old gentleman presented with a firm and tender mass involving the right epididymis. On examination, he was jaundiced. Computed tomography of the abdomen demonstrated an obstructive stricture of the extra-hepatic bile ducts, in keeping with a cholangiocarcinoma, through which a metal stent was endoscopically inserted for symptomatic relief. Subsequent right radical orchidectomy yielded a diffusely infiltrative adenocarcinoma obliterating the epididymis, extending into the rete testis, vas deferens and spermatic cord and showing widespread vascular and perineural invasion. Residual epididymal, rete, and testicular tubules showed no in situ neoplasia. Morphologically and immunohistochemically the features were in keeping with a metastasis from a primary cholangiocarcinoma. Conclusion Only two cases of bile duct carcinoma metastasising to the male genital tract have previously been reported in the literature, the testis being the main site of metastasis in both cases. To our knowledge, this is the first described case of cholangiocarcinoma metastasising primarily to the epididymis, and presenting as a solitary epididymal metastasis in the absence of disseminated disease. It serves to highlight the importance of performing a thorough examination of the male external genitalia both clinically, in the follow up of cancer patients, and at autopsy.